Coconut water combined with purebred chicken egg yolk as an alternative semen extender for Madura Pote bucks semen preservation - Tatik Hernawati; Susilowati, Suherni; Tri Wahyu Suprayogi; Widya Paramita Lokapirnasari; Zulfi Nur Amrina Rosyada (Universitas Airlangga, 2024)
One of the many efforts to increase the quality of livestock genetics is through artificial insemination (AI). Other than increasing it, AI can be conducted to preserve semen. A successful AI is determined by seminal quality, therefore, a method to preserve semen for a longer storage time is needed. The method used is adding an extender that fulfills prerequisites for a semen extender such as coconut water combined with egg yolk citrate extender. Coconut water is rich in carbohydrates, protein, vitamins, and antioxidants while egg yolk contains lecithin. This study aims to find out the Pote buck spermatozoa quality stored in coconut water and egg yolk extender. This study uses three groups of treatments (T0: 0.1 ml semen + 0.9 ml egg yolk citrate, T1: 0.1 ml semen + 0.9 ml coconut water, and T2: 0.1 ml semen + egg yolk citrate (20%) + coconut water). All three of these are stored at 5oC and evaluated every day until day 5 of their motility, viability, intact plasma membrane, abnormality, and MDA level. Data analysis used is ANOVA and a further test called BNT is conducted if a significant difference is determined. No significant difference was found between T0 and T1 (p>0.05). The highest progressive motility, viability, and intact plasma membrane (%) among the three groups of treatments happened to be from T2. Meanwhile, a low percentage of spermatozoa abnormality and MDA level were also found in T2 with its extender being coconut water combined with egg yolk citrate. To conclude, the best extender for storing Pote buck semen is stored at 5oC is coconut water combined with egg yolk citrate extender.